Is it just Luring Reported Profit? The Case of European Patent Boxes - Marko Köthenbürger; Federica Liberini; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2018)
Patent box regimes have become increasingly popular as an instrument to attract taxable income from intellectual property (IP). This paper assesses the quantitative impact of patent box regimes on profit shifting by multinational enterprises (MNEs). We proxy the ability to access the tax benefit of the patent box by historical IP ownership. On average, affiliates belonging to MNEs with historical IP ownership report, after the introduction of a patent box, 8.5 percent higher profit compared to their counterparts with no IP ownership. Patent boxes do not only lure reported profit. The pre-tax profit change is a net effect and thus also accounts for reversed internal debt shifting out of the country and productivity changes. The overall behavioral adjustments might lower corporate tax revenues. Further, the design of the patent box and the existence of a tax haven affiliate within an MNE turn out to be critical for the amount of profits shifted.
Keywords: H25; H26; F23; C21; C23; 330; corporate tax avoidance; patent box; multinational enterprise; profit shifting